2002
DOI: 10.1002/1099-0682(20021)2002:1<239::aid-ejic239>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Donor−Acceptor Interaction in Cationic Archetype Mono- and Dinuclear Sesquifulvalene Complexes [(η5-C5H5)Fe{µ-(η5-C5H4)(η7-C7H6)}M′L′]n+ (n = 1, 2)

Abstract: In order to gain a deeper insight into structure-property relationships of the donor (D)−acceptor (A) interactions in cationic sesquifulvalene complexes the mono-and dicationic complexes [(η 5 -C 5 H 5 )Fe{µ-(η 5 -C 5 H 4 )(η 7 -C 7 H 6 )}MЈLЈ] + were synthesized as BF 4 and PF 6 salts: MЈLЈ = Cr(CO) 3 (3PF 6 ); MЈLЈ = none (4BF 4 ); MЈLЈ = Ru(η 5 -C 5 H 5 ) + [5(PF 6 ) 2 ]; MЈLЈ = Ru(η 5 -C 5 Me 5 ) + [6(PF 6 ) 2 ]. The ferrocenyl substituent works as the electron donor and the tropylium moiety as the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…For example, the signals for the H3–H6 protons (see Scheme for nomenclature) for 3a – 6a are shifted upfield between 0.51 and 1.85 ppm in comparison with 2a , whereas the H8 proton in a position meta to the η 1 -coordinated nickelated ring only shows a difference of 0.01 ppm for 5a , 0.19 ppm for 4a, 0.28 ppm for 6a , and 0.46 ppm for 3a . The high-field shift of the aromatic protons on the ring supporting the π coordination of the second metal increase in the order [CpFe] + < [CpRu] + < [Cp*Ru] + < [Cr(CO) 3 ] and are in agreement with the electron-withdrawing properties of these fragments, as previously described …”
Section: Resultssupporting
confidence: 88%
“…For example, the signals for the H3–H6 protons (see Scheme for nomenclature) for 3a – 6a are shifted upfield between 0.51 and 1.85 ppm in comparison with 2a , whereas the H8 proton in a position meta to the η 1 -coordinated nickelated ring only shows a difference of 0.01 ppm for 5a , 0.19 ppm for 4a, 0.28 ppm for 6a , and 0.46 ppm for 3a . The high-field shift of the aromatic protons on the ring supporting the π coordination of the second metal increase in the order [CpFe] + < [CpRu] + < [Cp*Ru] + < [Cr(CO) 3 ] and are in agreement with the electron-withdrawing properties of these fragments, as previously described …”
Section: Resultssupporting
confidence: 88%
“…Therefore, solutions of the complex salts 3 – 5 in dichloromethane were subjected to hyper-Rayleigh scattering (HRS) measurements with a femtosecond pulsed laser source working at 800 nm. This wavelength ensures a larger degree of resonance enhancement for the signal, while the high repetition rate of the laser offers the possibility to differentiate between nonlinear scattering and potential multiphoton-induced fluorescence (MPF) by exploiting the demodulation and phase shift of the fluorescent signal in the frequency domain. MPF is of particular importance for polar ferrocene derivatives . However, high-frequency demodulation did not show any sign of MPF, although the signal was small and did not allow demodulation up to the full frequency bandwidth of the instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the hyperpolarization in the presence of irradiation provided by a femtosecond laser is too weak to be observed. An indication that the SHG would be rather low was already given by the low solvatochromic effect, which is, for example, considerably lower for the cationic compounds 3a and 3b than for the corresponding sesquifulvalenes. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are highly polarizable and exhibit the large second‐harmonic generation (SHG) effects 7. Heck and colleagues 8–11 reported a series of transition metal sesquifulvalene complexes with the large NLO response. They found that these organometallic complexes possessed the largest values of the first hyperpolarizabilities ever measured before.…”
Section: Introductionmentioning
confidence: 99%